2022
DOI: 10.1007/s40948-022-00454-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effects of two different cooling treatments on the physico-mechanical and microstructural properties of granite after high temperatures

Abstract: granites. The disintegration of the water-cooled granite samples increased considerably at 1000 °C and measurements could not be taken at this temperature. At the same temperature, water-cooling treatment caused microcracks and micropores, which led to more critical damage to the granite. These conclusions verify that different cooling methods have several effects on the physico-mechanical and microstructural properties of granite, and ensure a foundation for the prediction of rock mass behaviors in situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Nevertheless, real‐time high‐temperature experiments can better reveal the damage and failure mechanisms of deep rocks under thermo‐mechanical coupling due to their ability to replicate the in situ environment of high geo‐temperature and high geo‐stress for deep rocks accurately (Kumari et al., 2017; Yang et al., 2020). Studies have found that ambient temperature not only causes changes in the fundamental physical properties of rocks, such as density, longitudinal wave velocity, permeability, and thermal conductivity, but also significantly affects mechanical characteristics, including elastic modulus, Poisson's ratio, peak strength, inelastic deformation, acoustic emission events, and stress‐strain response (Gomah et al., 2022; Kahraman, 2022; Kumari et al., 2019; Sha et al., 2020; Srinivasan et al., 2022; Tang et al., 2019; Tang et al., 2022; F. Wang & Konietzky, 2019; L. N. Y. Wong et al., 2020; Yang et al., 2019). Overall, when the temperature increases, the stiffness and strength of hard rocks decrease; meanwhile, plastic deformation and creep characteristics become more pronounced, and the failure mode gradually transitions from brittle to ductile.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, real‐time high‐temperature experiments can better reveal the damage and failure mechanisms of deep rocks under thermo‐mechanical coupling due to their ability to replicate the in situ environment of high geo‐temperature and high geo‐stress for deep rocks accurately (Kumari et al., 2017; Yang et al., 2020). Studies have found that ambient temperature not only causes changes in the fundamental physical properties of rocks, such as density, longitudinal wave velocity, permeability, and thermal conductivity, but also significantly affects mechanical characteristics, including elastic modulus, Poisson's ratio, peak strength, inelastic deformation, acoustic emission events, and stress‐strain response (Gomah et al., 2022; Kahraman, 2022; Kumari et al., 2019; Sha et al., 2020; Srinivasan et al., 2022; Tang et al., 2019; Tang et al., 2022; F. Wang & Konietzky, 2019; L. N. Y. Wong et al., 2020; Yang et al., 2019). Overall, when the temperature increases, the stiffness and strength of hard rocks decrease; meanwhile, plastic deformation and creep characteristics become more pronounced, and the failure mode gradually transitions from brittle to ductile.…”
Section: Introductionmentioning
confidence: 99%